Heranças invisíveis: transmissão psíquica e fragmentação do eu na psicose - Haas, Tábata Rech (My University, 2025)
This undergraduate thesis addresses psychosis and its possible relations with psychic transmission, specifically within the mother-daughter relationship. Developed from a psychoanalytic perspective, it seeks to understand how the fragmentation of personality observed in psychosis may be linked to the effects of transgenerational psychic transmission. The general objective was to discuss the possible relationships between these phenomena, while the specific objectives were: to characterize psychosis, to conceptualize transgenerational psychic transmission from a psychoanalytic standpoint, and to present the mother-daughter relationship based on the fundamentals of psychoanalytic theory. The literature review encompassed classical psychoanalytic authors, such as Freud and Lacan, as well as contemporary scholars like Kaës, Abraham, and Torok, who have dedicated their research to psychic transmission and family dynamics. The methodological approach was qualitative, with a theoretical's bibliographic design and an exploratory analysis of a cultural artifact - the film Black Swan (2010), directed by Darren Aronofsky. In the discussion, the first category explored the symbiotic relationship and maternal bond, revealing a fusional and invasive dynamic that hinders symbolic separation and keeps the daughter in an infantilized position. The second category examined personality fragmentation in psychosis, understood as the result of a failure in the symbolization of lack and the absence of the paternal function, which leads to a loss of ego anchoring and to the blurring of boundaries between reality and delusion. Finally, the third category addressed psychic transmission, demonstrating how the unelaborated desires, frustrations, and ideals of one generation may be unconsciously imposed upon the next, becoming mandates that confine the subject within a familial narrative. The final considerations indicate that when the mother-daughter relationship is permeated by invasion and the absence of a mediating third, unrepresented contents are perpetuated, compromising the subject's psychic constitution. Thus, it is understood that psychic transmission, when operating intrusively and without symbolic elaboration, may reduce the psyche to fragmentation, as the subject becomes the depository of an inherited psychic burden that prevents the development of an autonomous identity. This study therefore contributes to a broader understanding of the effects of transgenerational transmission on the structuring of the ego and encourages reflection on the possibilities of symbolically elaborating these inherited legacies within the clinical and theoretical field of psychoanalysis. [resumo fornecido pelo autor]
O presente Trabalho de Conclusão de Curso tem como tema a psicose e suas possíveis relações com a transmissão psíquica, especificamente na relação mãe-filha. A pesquisa se desenvolve sob a perspectiva psicanalítica, buscando compreender de que modo a fragmentação da personalidade observada na psicose pode estar vinculada aos efeitos da transmissão psíquica transgeracional. O objetivo geral consistiu em discutir as possíveis relações entre esses fenômenos; para isso, os objetivos específicos foram: caracterizar a psicose, conceituar a transmissão psíquica transgeracional sob a ótica da psicanálise e apresentar a relação mãe-filha com base nos fundamentos da teoria psicanalítica. A revisão da literatura abrangeu autores clássicos da psicanálise, como Freud e Lacan, e autores contemporâneos, como Kaës, Abraham e Torok, dedicados ao estudo da transmissão psíquica e das dinâmicas familiares. O método adotado foi qualitativo, com delineamento teórico-bibliográfico e análise de artefato cultural, de caráter exploratório, tendo como objeto o filme Cisne Negro (2010), de Darren Aronofsky. Na discussão, a primeira categoria abordou a relação simbiótica e o vínculo materno, evidenciando uma dinâmica fusional e invasiva que impede a separação simbólica e mantém a filha em posição infantilizada. Em seguida, analisou-se a fragmentação da personalidade na psicose, compreendida como resultado da falha na simbolização da falta e da ausência da função paterna, o que conduz à perda de ancoragem do Eu e à dissolução dos limites entre realidade e delírio. Por fim, discutiu-se a transmissão psíquica, revelando como os desejos, frustrações e ideais não elaborados de uma geração podem ser depositados na seguinte, transformando-se em mandatos inconscientes que aprisionam o sujeito à história familiar. As considerações finais indicam que a relação entre mãe e filha, quando permeada pela invasão e pela ausência de um terceiro mediador, favorece a perpetuação de conteúdos não simbolizados que comprometem a constituição subjetiva. Assim, compreende-se que a transmissão psíquica, ao operar de forma intrusiva e sem elaboração, pode reduzir o psiquismo à fragmentação, na medida em que o sujeito é tomado como depositário de uma herança psíquica que o impede de construir uma identidade própria. O estudo contribui, portanto, para ampliar a compreensão dos efeitos da transmissão transgeracional na estruturação do Eu e para refletir sobre as possibilidades de elaboração simbólica dessas heranças no campo clínico e teórico da psicanálise. [resumo fornecido pelo autor]
Keywords: Psicanálise; Psicoses; Mãe e filha; Psicologia